1997
DOI: 10.1111/j.1600-0897.1997.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforin‐Expressing Lymphocytes in Peripheral Blood and Decidua of Human First‐Trimester Pathological Pregnancies

Abstract: Our results show that significant decreases in the prevalence of perforin-positive lymphoid cells, their subpopulations, and mean fluorescence intensity for perforin are associated with pregnancy failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…NK cell-mediated cytolysis is highly dependent on perforin, which induces lysis and promotes the death of target cells33. It has been reported that more than 95% of all decidual CD56 bright cells expressed perforin3435, and appropriate perforin levels plays an important role in embryo implantation and maintaining normal human pregnancy. One study illustrated a slightly higher distribution of perforin-positive uNK cells in human sporadic miscarriages with a normal foetal chromosomal karyotype36, implying that higher perforin level might be harmful to the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…NK cell-mediated cytolysis is highly dependent on perforin, which induces lysis and promotes the death of target cells33. It has been reported that more than 95% of all decidual CD56 bright cells expressed perforin3435, and appropriate perforin levels plays an important role in embryo implantation and maintaining normal human pregnancy. One study illustrated a slightly higher distribution of perforin-positive uNK cells in human sporadic miscarriages with a normal foetal chromosomal karyotype36, implying that higher perforin level might be harmful to the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients suffering from miscarriages and anembryonic pregnancies, the number of perforin-positive cells in the decidual tissue was markedly decreased (Gulan et al, 1997). On the other hand, the number of IL-2 receptor positive cells was noticeably increased in the decidua tissue derived from patients with recurrent spontaneous abortions (Quack et al, 2001).…”
Section: Article In Pressmentioning
confidence: 98%
“…However, DMCs might be ineffective in harming trophoblast cells owing to a relative decrease in the frequency and mean fluorescence intensity of perforin in unstimulated CD56 + decidual NK cells in missed abortions. 38 In addition, functionally active 19 and progesterone-producing 39 trophoblast cells possess immunomodulatory properties. 40 All these mechanisms could be responsible for the early termination of pregnancy with retention of fertilization products.…”
Section: The Effect Of Hsp70 On Colocalization Of Lamp-1 and Granulmentioning
confidence: 99%